STUDY ON THE DEVELOPMENT OF INDIVIDUAL TECHNIQUE IN FOOTBALLERS OF 10 TO 12 YEARS - Cătălin-Andrei Tatarcan (Editura Univeristatii "Stefan cel Mare" din Suceava, 2020)
The present study is based on the experiment method and also on the observation method, applied over two groups of footballers between the ages of 10 and 12 years. Both groups submitted a technical test / technical route. The players in the first group, the target group, repeated the technical route during the training sessions, trying to selfimprove the time of crossing the route. The final results showed that the individual technique of the children in the target group was improved, and the technical route time was decreased.